Nghiên cứu phản ứng khâu mạch và tính chất của một số hệ trên cơ sở nhựa epoxy biến tính dầu thực vật. I - Ảnh hưởng của cấu tạo hóa học dầu thực vật đến phản ứng khâu mạch quang hóa. - Hiền, Lê Xuân; Hoàng, Vũ Minh; Việt Triều, Nguyễn Thị (Vietnam Journal of Chemistry, 2014)
The influence of the chemical structure of the oils on the photocrosslinking of the photocrosslinkable systems on the base of the epoxy resin modified by tung oil (ETT39), linseed oil (EL39), soya-bean oil (ED39), rubber seed oil (EHCS39) and biscycloaliphatic diepoxy monome Cyracure 6105 (6105), triarylsulfonium salt (TAS) or hexanendiol diacrylate (HDDA), I.184 have been studied. It was determined that under exposure to the 250 mW/cm2 UV lamp the fastest and highest decay of the TAS was observed in the cationic photopolymerisation system ETT39-6105-TAS. Although the convertion rate of total epoxy groups in the photocrosslinkable systems at the beginning of the photocrosslinking was affected by the type of the oil in the modified resin and arranged in the order: EHCS 39 > ED 39 > EL 39 > ETT 39, the final conversion of total epoxy groups in the systems containing ETT 39 and EL 39 was higher than in systems with ED 39 and EHCS 39. The photocrosslinking of the photocrosslinkable systems on the base of the vegetable oils modified epoxy resin and HDDA, I.184 was followed by the decrease of the total and HDDA acrylate double bonds. The influence of the type of the oil in the modified resin on the conversion of the double bonds in the systems was also investigated.